Peran Hutan Kota Sonokridanggo Boyolali Sebagai Penghasil Oksigen - Safitri, Olinda Ayu; Astining Putri, Rani Rachma; Fajri, Roifah; Nurafni Rindiani (Jurnal Informasi, Sains dan Teknologi, 2024)
The increase in population in Boyolali Regency, which reached 1,090,131 people in 2023, has a significant impact on environmental quality, especially air quality. This study aims to calculate the oxygen produced by Sonokridanggo Urban Forest, covering an area of 2,500 m², which functions as a green open space (RTH). The methods used include measuring tree trunk diameter using the diameter breast height (dbh) method and calculating biomass and stored carbon using the allometric formula. The results showed that Ketapang (Pterocarpus indicus) species had the highest carbon storage ability, which was 16,159.67 kg, and absorbed 59,252.13 kg CO₂ equivalent, making it the main contributor to oxygen production. Overall, Sonokridanggo Urban Forest produces 401,699.18 kg of oxygen per year, enough to meet the oxygen needs of 1,274 people. Among the existing tree species, Ketapang is the largest oxygen producer with a contribution of 158,005.69 kg per year. With a contribution of about 0.11% of the total oxygen demand of Boyolali residents.